Steerable parametric loudspeaker with preprocessing methods - Gan, Woon-Seng (2013)
The emerging applications of the parametric loudspeaker, such as 3D audio, require both directivity control and high fidelity at the audible frequency (i.e. the difference frequency of the primary frequencies generated by the parametric loudspeaker). Although the phased array techniques have been applied and proved adequate to adjust the steering angles of the parametric loudspeaker, and preprocessing methods have been studied to reduce the harmonic distortions, there is no published work on the effectiveness of the combination of the beamsteering method and the preprocessing methods for the broadband steerable sound beam system. This paper aims to investigate on this unexplored problem. Firstly, the relation between the phases of the primary waves and the difference frequency wave is explored to prove the feasibility of achieving a broadband steerable sound beam from the parametric loudspeaker with preprocessing methods. Secondly, based on the derived relation, the beamsteering structure is proposed. Lastly, preprocessing methods are proposed for the steerable parametric loudspeaker using double sideband modulation (DSBAM) and square root amplitude modulation (SRAM) methods. Spatial performances of the steerable parametric loudspeaker with preprocessing methods are presented in this paper.